Exploring the Influence of Biochar-Supported Nano-Iron Oxide on Phosphorus Speciation Transformation and Bacterial Community Structure in Aerobic Pig Manure Composting Processes - Ning Yuan; Kang Wang; Mengyue Liang; Jia Zhou; Rui Yu (Microorganisms)
Existing studies have demonstrated the positive effects of nano-sized iron oxide on compost maturity, yet the impact of nano-sized iron oxide on phosphorus speciation and bacterial communities during the composting process remains unclear. In this study, pig manure and straw were used as raw materials, with biochar-supported nano-sized iron oxide (BC-Fe3O4NPs) as an additive and calcium peroxide (CaO2) as a co-agent, to conduct an aerobic composting experiment with pig manure. Four treatments were tested: CK (control), F1 (1% BC-Fe3O4NPs), F2 (5% BC-Fe3O4NPs), and F3 (5% BC-Fe3O4NPs + 5% CaO2). Key findings include the following. (1) BC-Fe3O4NPs increased compost temperatures, with F3 reaching 61℃; F1 showed optimal maturity (C/N ratio: 12.90). (2) BC-Fe3O4NPs promoted stable phosphorus forms; Residual-P proportions were higher in F1, F2, and F3 (25.81%, 51.16%, 51.68%) than CK (19.32%). (3) Bacterial phyla Firmicutes, Actinobacteria, and Proteobacteria dominated. BC-Fe3O4NPs altered community composition, especially on day 7. Firmicutes dominated CK, F1, and F3; Proteobacteria dominated F2. At the genus level, day 7 showed Corynebacterium (CK), Clostridum (F1, F3), and Caldibacillus (F2) as predominant. (4) Pearson correlation analysis revealed shifted correlations between phosphorus forms and bacterial phyla after BC-Fe3O4NPs addition. Firmicutes positively correlated with NaOH-OP in F1 during the thermophilic phase, facilitating phosphate release and adsorption by BC-Fe3O4NPs. The significance of correlations diminished with increasing additive concentration; in F3, all phyla positively correlated with various phosphorus forms.